The Use of Podcasting Technology to Develop EFL Learners’ Listening Skills - Isaadah, Khoirunisa; Rizal, Daviq (Jurnal Bahasa Inggris, 2024)
The rise of information and communication technology has led to the development of various new teaching and learning methods for English. Podcasting is one such method that teachers are using to enhance language skills and promote outside-of-classroom learning. This study investigates the use of podcasting technology to develop EFL learners’ listening skills. It employed a quantitative descriptive design involving 48 EFL students from the English Education program at a state university in Semarang, Indonesia. Data were collected through a questionnaire exploring students’ experiences, perceptions, benefits, and challenges of using podcasts for listening practice. The findings indicate that most students responded positively to podcast-based learning and perceived podcasts as helpful in improving their listening comprehension, particularly due to their authenticity, accessibility, and flexibility. However, students also reported challenges, especially related to speech speed and comprehension difficulties. These findings highlight the potential of podcasting technology as an effective supplementary medium for developing listening skills and emphasize the importance of integrating podcast-based listening activities into EFL instruction at both university and secondary school levels.